2019
DOI: 10.1177/1098612x19867777
|View full text |Cite
|
Sign up to set email alerts
|

Welfare of cats 5–29 months after perineal urethrostomy: 74 cases (2015–2017)

Abstract: Objectives The objective of this study was to evaluate the long-term quality of life in cats following perineal urethrostomy. Methods This study comprised a retrospective case series of 74 cats with urinary obstructions that received perineal urethrostomies at the American Society for the Prevention of Cruelty to Animals (ASPCA) Animal Hospital between September 2015 and July 2017. Medical records were reviewed for information on the number of obstructions prior to surgery, urinary tract problems at the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…These figures are comparable to previous reports of owner-rated quality of life following PU surgery, where 75–88% of cats were judged as having a moderate-to-good quality of life. 2,10 However, they are contradicted by another study, which reports a satisfaction rate of 33.3% among owners of cats undergoing PPU, which was significantly lower than the 81.8% satisfaction among owners of cats undergoing PU. 5 This difference in PPU satisfaction may be due to indication for urethrostomy, rather than surgical technique.…”
Section: Discussionmentioning
confidence: 95%
“…These figures are comparable to previous reports of owner-rated quality of life following PU surgery, where 75–88% of cats were judged as having a moderate-to-good quality of life. 2,10 However, they are contradicted by another study, which reports a satisfaction rate of 33.3% among owners of cats undergoing PPU, which was significantly lower than the 81.8% satisfaction among owners of cats undergoing PU. 5 This difference in PPU satisfaction may be due to indication for urethrostomy, rather than surgical technique.…”
Section: Discussionmentioning
confidence: 95%
“…Other causes include urolithiasis (10 to 35 per cent of cases), of which calcium oxalate and struvite are both common types of stones. Slater and others (2020) also found strictures and urethral trauma to be present in 15 per cent of cases. Blood clots occur occasionally, as can neoplasia of the urethra, prostate or bladder.…”
mentioning
confidence: 84%
“…All analyses were conducted using R version 3.6.3 ( 21 ). Linear mixed models assessed whether there were main effects of study condition and test timing (i.e., pretest or post-test) on study measures.…”
Section: Methodsmentioning
confidence: 99%
“…As another example of incremental care, researchers at Colorado State University have demonstrated that an outpatient treatment protocol for select puppies diagnosed with parvovirus may be a reasonable and less costly alternative to inpatient hospitalization ( 20 ). A spectrum of care treatment option might be to manage a feline obstruction case by performing a perineal urethrostomy earlier in the disease course rather than conservatively managing the problem with multiple costly emergency visits ( 21 ). Another spectrum of care treatment option is the timely referral of pyometra cases to spay-neuter clinics rather than performing emergency surgery in full-service clinics ( 22 ).…”
Section: Introductionmentioning
confidence: 99%